Manajemen ICU pada Pasien dengan HIV-AIDS - Catur Prasetyo Wibowo; Akhmad Yun Jufan (Lembaga Pengembangan Kinerja Dosen, 2026)
Patients with immune system disorders, whether congenital or acquired, represent a high-risk group for severe infections, particularly when admitted to the Intensive Care Unit (ICU). Immune disorders can occur as primary immunodeficiencies, such as IgA Deficiency and DiGeorge Syndrome, or as secondary immunodeficiencies caused by chronic infections like HIV/AIDS or the use of immunosuppressive therapy in post-transplant patients and those with autoimmune diseases. These conditions reduce the body’s ability to fight pathogens, thereby increasing susceptibility to life-threatening opportunistic infections. Specifically, patients with HIV/AIDS face a high risk of severe infectious complications due to a decrease in CD4 cell count below 250 cells/mm³, which significantly worsens the clinical prognosis. The HIV/AIDS epidemic has become a major global health problem with substantial impacts on morbidity, mortality, and economic burden, particularly as it affects the productive age group. Therefore, understanding the mechanisms of immune dysfunction and developing effective infection prevention strategies in immunodeficient patients are essential to improving ICU care outcomes and reducing mortality rates.